Modeling drivers of biodiversity change emphasizes the need for multivariate assessments and rescaled targeting for management. Issue 10 (24th August 2022) - Dajka, Jan‐Claas; di Carvalho, Josie Antonucci; Ryabov, Alexey; Scheiffarth, Gregor; Rönn, Lena; Dekker, Rob; Peters, Kimberley; Leberecht, Bo; Hillebrand, Helmut
Abstract: The current policy and goals aimed to conserve biodiversity and manage biodiversity change are often formulated at the global scale. At smaller scales however, biodiversity change is more nuanced leading to a plethora of trends in different metrics of alpha diversity and temporal turnover. Therefore, large‐scale policy targets do not translate easily into local to regional management decisions for biodiversity. Using long‐term monitoring data from the Wadden Sea (Southern North Sea), joining structural equation models and general dissimilarity models enabled a better overview of the drivers of biodiversity change. Few commonalities emerged as birds, fish, macroinvertebrates, and phytoplankton differed in their response to certain drivers of change. These differences were additionally dependent upon the biodiversity aspect in question and which environmental data were recorded in each monitoring program. No single biodiversity metric or model sufficed to capture all ongoing change, which requires an explicitly multivariate approaches to biodiversity assessment in local ecosystem management.